Tumor location does not limit percutaneous treatment of small renal masses with microwave ablation - Meng, Xiaosong; Ghandour, Rashed; Margulis, Vitaly (Annals of Translational Medicine, 2019)
The global incidence of renal cell carcinoma (RCC) has steady increased over the past two decades and accounts for 5% of all cancers in men and 3% of all cancers in women (1). This rising incidence is likely due to increased detection of small renal masses (SRMs), characterized as ≤4 cm in size, on cross-sectional imaging for other conditions (2).